If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4 + -3i)(5 + i) = 0 Multiply (4 + -3i) * (5 + i) (4(5 + i) + -3i * (5 + i)) = 0 ((5 * 4 + i * 4) + -3i * (5 + i)) = 0 ((20 + 4i) + -3i * (5 + i)) = 0 (20 + 4i + (5 * -3i + i * -3i)) = 0 (20 + 4i + (-15i + -3i2)) = 0 Combine like terms: 4i + -15i = -11i (20 + -11i + -3i2) = 0 Solving 20 + -11i + -3i2 = 0 Solving for variable 'i'. Factor a trinomial. (4 + -3i)(5 + i) = 0Subproblem 1
Set the factor '(4 + -3i)' equal to zero and attempt to solve: Simplifying 4 + -3i = 0 Solving 4 + -3i = 0 Move all terms containing i to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3i = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3i = 0 + -4 -3i = 0 + -4 Combine like terms: 0 + -4 = -4 -3i = -4 Divide each side by '-3'. i = 1.333333333 Simplifying i = 1.333333333Subproblem 2
Set the factor '(5 + i)' equal to zero and attempt to solve: Simplifying 5 + i = 0 Solving 5 + i = 0 Move all terms containing i to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + i = 0 + -5 Combine like terms: 5 + -5 = 0 0 + i = 0 + -5 i = 0 + -5 Combine like terms: 0 + -5 = -5 i = -5 Simplifying i = -5Solution
i = {1.333333333, -5}
| 2n-3(4n+5)=-6+17 | | 2(x-7)=15 | | 4x-2[2-3(3-5x)]=1 | | 4x-2[2-3(3-4x)]=1 | | 2(3x-7)+4=10 | | -7y+3+8y=12-20 | | 2(6x-5)(4x+5)=0 | | -5-5=0 | | 3+log^4(2x+6)=6 | | -16=-2(3+x) | | (-4i)(6i)=0 | | x+2=-2x+14 | | 4(2n-3)=(5n+4)+3 | | [2x+5]=14 | | 20=-36x-4(-6-2) | | 4-(7y-5)=6y-4 | | -16x^2+50x+15=0 | | (ax+by)(cx+y)=x | | 20x+5=21x-5 | | 20x=21x | | 80=(10+30p)-(150+20p) | | 10a+7=6a+10+3a | | 6(2x-7)+4=12x-38 | | -8u+30=2u | | x+3=-4x+23 | | 16x^2+50x+15=0 | | 18-(1/22)(2x)=9-(1/22)(x) | | (4x+5)(5x-1)=0 | | 2x+0.5x=770 | | log^2(x-1)=4 | | (2/3)(x+4)=(3/8)(x-3) | | 3x-8=4x-25 |